Les transactions économico-sexuelles : actrices et acteurs, institutions et territoires - Salomé Donzallaz; Olivier Crevoisier (Netcom)
This paper adopts the hypothesis put forward by Tabet (2004; 2001), according to which sexual transactions are always embedded within an economic framework, and seeks to illustrate how this embeddedness is presented today with a digital case study. Sexual Economic Transactions (SET) are approached from an institutionalist and territorial perspective, enabling us to supplement Tabet's structuralist framework and capture the changes that are underway. The aim is to identify the relational, institutional and computational modalities of SETs, and to propose an ideal-type based on Commons' transaction theory ([1934], 1989). In order to understand the interconnection between SETs and the rest of society, in the second section we identify a typology of territorialities, using the oppositions between public and private spaces on the one hand, and commercial and domestic spaces on the other. Taking as our starting point the idea that SETs have historically constituted activities that structure these oppositions, in the third section we examine how digitization today affects their inclusion in society through the case of sex cams. In conclusion, we propose the hypothesis that SETs have in the past assumed a character that threatens to jeopardize social order, and have always been subject to heavy control, particularly within the public commercial space. This control is today digitally reinvented by certain forms of avoidance of the “whore stigma” (Pheterson, 1993), while creating even greater separation between the public and commercial sphere on the one hand and the commercial force of female sexuality on the other.